The Dynamics of the Role of Land Office Mediators in Facilitating Settlement Agreements in Land Disputes - Muhenri Sihotang; Riswadi Riswadi (Asian Journal of Social and Humanities, 2024)
Land disputes are legal issues that arise when there are overlapping or conflicting claims or demands regarding land rights among different parties. This study examines the role of Land Office mediators in resolving land disputes in Indonesia, focusing on challenges and strategies to enhance mediation effectiveness. The research identifies obstacles such as limited legal understanding among mediators, unclear procedures, pressure from third parties, and uncooperative attitudes from disputing parties. A normative legal research method, supported by legislative and conceptual approaches, is employed to analyze relevant laws and mediation practices. Findings indicate that effective mediation requires improving mediator capacity, standardizing procedures, fostering cooperation with stakeholders, and raising public awareness. Solutions proposed include targeted mediator training, developing clear protocols, and creating an enabling environment for constructive dialogue. These measures are expected to enhance the mediation process, ensuring fair and sustainable outcomes while promoting social harmony and economic stability in land management.